Optimization Of The Learning Process Of Basketball Exercises - U. A. Farmonov (Research Parks Publishers, 2021)
The article raises the problem of optimization of the educational process in physical education classes at the basketball department. Among the students of 1-2 courses aged 17-20 years old, who go in for basketball, priority motives were identified that played a major role in the choice of this sport out of fifteen others presented at the Faculty of Physical Education of BSU.